Advanced scintillation single crystals based on complex oxides with large atomic number - Burachas, S.F.; Nagornaya, L.L.; Onishchenko, G.M.; Piven, L.A.; Pirogov, E.N.; Ryzhikov, V.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
An improved production technology has been developed for scintillation single crystals based on complex oxides with large atomic number – bismuth germanate (BGO), gadolinium silicate (GSO), cadmium tungstate (CWO) and lead tungstate (PWO). Scintillators based on these crystals have good energy resolution and light output, high detection efficiency, they are not hygroscopic, have high radiation stability and mechanical strength. This makes it possible to use them as radiation detectors for high energy physics (PWO), in instruments for radiation and radioecological monitoring (BGO,CWO,GSO).